Behavioral Differences Across Theta Burst Stimulation Protocols. A Study on the Sense of Agency in Healthy Humans - Zito, Giuseppe A.; Worbe, Yulia; Lamy, Jean-Charles; Kälin, Joel; Bühler, Janine; Weber, Samantha; Müri, René M.; Aybek, Selma (Frontiers in Neuroscience, 2021)
Background Theta burst stimulation (TBS) is a non-invasive brain stimulation method. Various stimulation protocols have been proposed, for instance stimulation at 50 Hz with pattern at 5 Hz, or at 30 Hz with pattern at 6 Hz. To identify better stimulation parameters for behavioral applications, we investigated the effects of 50-Hz continuous TBS (cTBS) on the sense of agency (SoA), and compared them with a previously published study with 30-Hz cTBS. Methods Based on power analysis from a previous sample using two applications of 30-Hz cTBS, we recruited 20 healthy subjects in a single-blind, Vertex-controlled, randomized, crossover trial. Participants were stimulated with one application of 50-Hz cTBS over the right posterior parietal cortex (rPPC), a key area for agency processing, and the vertex, in a random order. A behavioral task targeting the SoA was done before and after stimulation. After controlling for baseline differences across samples, we studied the effect of stimulation in the two protocols separately. Results Compared to the previously published 30-Hz protocol, 50-Hz cTBS over the rPPC did not reveal significant changes in the SoA, similar to sham Vertex stimulation. Conclusions One application of 50-Hz cTBS was not sufficient to elicit behavioral effects, compared to two applications of 30-Hz cTBS, as previously described. This may be due to a mechanism of synaptic plasticity, consolidated through consecutive stimulation cycles. Our results are relevant for future studies aiming at modulating activity of the rPPC in cognitive domains other than agency, and in patients affected by abnormal agency, who could benefit from treatment options based on TBS.